MULTIPLE INTELLIGENCES AND THEIR INFLUENCE ON THE DEVELOPMENT OF THE APPLIED LINGUISTICS SCHOOL STUDENTS ORAL SKILLS AT PUCE ESMERALDAS, 2017 - Dominguez Viteri, Alberto Francisco (2018)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés